Multicultural public administration: Effects of language diversity and dissimilarity on public employees' attachment to employment. (11th October 2017) - Ritz, Adrian; Alfes, Kerstin
Abstract : A major part of research in public administration focuses on the impact of ethnic diversity on outcomes such as performance and turnover, and on the management of diversity with regard to different employee groups. Recent research, however, shows the relevance of relational demography in the context of employee inclusion in public organizations. So far, most studies have been based on ethnic differences in countries that can be described as mononational and monolinguistic. The current study advances this stream of research by investigating how diversity and dissimilarity measures affect public employees' attachment to employment in a multicultural public administration in Switzerland. Evidence from a hierarchical multilevel analysis revealed that language diversity and the support for diversity from supervisors affected individuals' attachment. However, our findings on individuals' language dissimilarity related to the inclusion of minorities did not support the assumed crowding‐out effect between diversity and dissimilarity. Implications and avenues for future research are discussed.